Effects of Guided Written Disclosure Protocol on mood states and psychological symptoms among parents of off-therapy acute lymphoblastic leukemia children. (June 2013) - Martino, Maria Luisa; Freda, Maria Francesca; Camera, Flavia
This study assesses the effects of Guided Written Disclosure Protocol on psychological distress in mothers and fathers of off-therapy acute lymphoblastic leukemia children. An experimental group participated in the writing intervention with a control group subject only to test-taking standards. The Symptom Questionnaire and Profile of Mood States were administered at baseline, post-intervention, and follow-up. Guided Written Disclosure Protocol had significant effects on the progressive reduction of anxiety, depression, somatic symptoms, hostility, tension–anxiety, and fatigue–inertia within the experimental group. However, the control group distress levels tended to worsen over time. The mediating role of emotional processing was highlighted.